Geometric changes in the aortic valve annulus during the cardiac cycle: impact on aortic valve repair. (5th March 2018) - Petersen, Johannes; Voigtländer, Lisa; Schofer, Niklas; Neumann, Niklas; von Kodolitsch, Yskert; Reichenspurner, Hermann; Girdauskas, Evaldas
Abstract: OBJECTIVES: The growing experience in aortic valve (AV) repair showed that annular stabilization is a crucial component to achieve stable long-term results after AV repair. Dynamic changes in the AV annulus during the cardiac cycle may have an impact on annuloplasty design. METHODS: We retrospectively analysed full cardiac cycle multislice computed tomography data from 58 consecutive patients (mean age 75.9 ± 6.5 years, 36% men) with normally functioning tricuspid AVs (normal AV subgroup). The following computed tomography parameters were measured during systole and diastole: maximum, minimum and mean AV annulus diameter, AV annular area and AV annular perimeter. The AV annular eccentricity index was calculated (%) [(max AV annulus × 100/min AV annulus) – 100] in systole and diastole. Subsequently, multislice computed tomography data from 20 patients with severe aortic regurgitation were analysed [aortic valve regurgitation (AR) subgroup]. RESULTS: In the normal AV subgroup, there was a significant decrease in the mean AV annulus diameter from systole to diastole (i.e. 24.6 ± 2.5 mm vs 23.9 ± 2.4 mm, respectively; P < 0.001), which occurred predominantly in the short annular axis (i.e. 21.2 ± 2.4 mm in systole vs 19.9 ± 2.3 mm in diastole; P < 0.001). The mean AV annular area decreased significantly in diastole (i.e. 467.5 ± 94.5 mm 2 in systole vs 444.8 ± 86.1 mm 2 in diastole; P = 0.012). The annular eccentricity index increased significantly in diastole (33.0 ± 12.2% in systole vs 41.4 ± 13.5% in diastole; P < 0.001). Furthermore, we found an inverse linear correlation between the mean AV annulus diameter and the annular eccentricity index ( r = −0.40, P = 0.034). The diastolic annular eccentricity index was significantly reduced in the AR subgroup (i.e. 41.4 ± 13.5% in the normal AV subgroup vs 33.7 ± 14.8% in the AR cohort; P = 0.035). CONCLUSIONS: The normal AV annulus undergoes important geometric deformation during the cardiac cycle that is significantly reduced in diastole in the AR scenario. A novel AV annuloplasty system should ideally adapt for this marked diastolic annular eccentricity and thereby allow for dynamic aortic root changes during the cardiac cycle.